Hidden supply chain risk and Incoterms®: Analysis and mitigation strategies - Jonathan Davis; John Vogt (Journal of Risk and Financial Management, 2021)
Among the many sources of financial and operational risk in supply chains are the Incoterms®, which are terms of trade used to decide who does what in a cargo movement, when risk passes from seller to buyer and who pays for which part of the movement. Wrong Incoterms® create unexpected costs or risks, at best, and inoperable contracts at worst, with all the challenges implied. This paper analyzes risk in supply chain management (SCM) through the lens of the responsibilities and costs imposed by Incoterms®. The authors also conducted a survey of 100 supply chain decision makers on supply chain contracts creation and Incoterms® knowledge in the population. Failure mode and effect analysis (FMEA) of Incoterms® reveals many scenarios that pose financial, operational, and even legal risk to firms. Results suggest Incoterms® rules are poorly understood by supply chain practitioners in general, are often chosen by personnel who are not aware of the implications of their choices, and are therefore frequently chosen incorrectly or non-strategically, thereby increasing cost and risk. This paper discusses the implications of the analysis and survey results on supply chain performance as well as mitigation strategies for practitioners in strategically using Incoterms® to remove cost, risk, and delay from supply chain transactions.
Keywords: 330; Incoterms®; supply chain risk; risk management; logistics; procurement cycle risk; terms of trade